SIMPLE AND RAPID CULTIVATION OF TRYPANOSOMA DANILEWSKYI STRAIN FCC-1 IN MONOPHASIC LIQUID CULTURE MEDIUM - M. S. Ahmed; K. S. Ahmed; W. A. Khan; H. Ali; F. Ollevier; D. L. Ray (Journal of Animal and Plant Sciences, 2014)
Trypanosoma danilewskyi strain F Cc-1 was isolated from the blood of a laboratory infected juvenile common carp.  Trypanosomes (blood stream forms) were first adapted to culture conditions in Tobie’s medium.  Ten sterilized glass culture tubes each containing 2 ml of Tobie’s medium solidified in slants and covered with 1 ml Locke-Krebs overlay, were inoculated with 0.1 ml of infected blood containing 1x 105 live trypanosomes and incubated at 20º C.  Tobie's medium supported growth and trypanosomes were well adapted to culture conditions because small colonies were seen in 6th and 7th subculture.  The adapted trypanosomes were re-inoculated in a monophasic liquid culture medium (L4 NHS).  Ten sterilized caped glass culture tubes, each containing 3 ml of medium, were inoculated with 0.1 ml culture containing 3 x 105 flagellates and incubated at 20º C.  Trypanosome propagation / multiplication were examined on day 3 p.i. and daily later on and their number ml-1 was estimated by the Rapid Matching Method.  Trypanosomes growth obtained in L4 NHS culture medium on day 7-8 was 5.0 ± 0.56 x 106 live trypanosomes ml-1.  The trypanosome number significantly (P<0.05) increased from day 3 to 8 as compared to day 1.  Flagellate numbers remained high until day 10 but decreased from day 12-15 p.i.  L4 NHS, mono-phasic culture medium supported growth of T. danilewskyi strain FCc-1 (culture forms) significantly high (P<0.01) at 20º C and found the best for rapid fish trypanosome culture.
Keywords: rapid culture; monophasic medium; strain F Cc-1; L4NHS; blood flagellates; fish